EFFECT OF SILYMARIN ON SERUM LEVELS OF ALT AND GGT IN ETHANOL INDUCED HEPATOTOXICITY IN ALBINO RATS - Rehman, Muhammad Habib-ur-; Mahmood, Tariq; Salim, Taher; Afzal, Naeema; Ali, Nasir; Iqbal, Javed; Tahir, Muhammad; Khan, Asif (Journal of Ayub Medical College Abbottabad, 2009)
Background: Alcoholic liver disease is a worldwide health problem. At least 80% of heavy drinkers have been reported to develop steatosis, 10-35% alcoholic hepatitis, and approximately 10% liver cirrhosis. The objective of this study was to determine the effect of silymarin on the levels of serum ALT and GGT in ethanol induced hepatotoxicity in albino rats. This study was an experimental Randomised Control Trial (RCT), and was conducted at the experimental research laboratory of University of Health Sciences, Lahore, from January 2007 to December 2007. Methods: Eighteen male albino rats of 6-8 weeks age, weighing 150-200 gm each were divided into 3 groups of 6 rats each. Group A served as control, Group B was given ethanol at a dose of 0.6 ml (0.5 gm)/100 gm/day and group C was given ethanol and silymarin at a dose of 0.5 gm/100 gm/day, and 20 mg/100 gm/day respectively for 8 weeks. At the end of the experiment, each animal was euthenised with chloroform. Blood was drawn from each animal by cardiac puncture for liver function tests (ALT and GGT). After taking blood sample, each euthenised animal was sacrificed and then its liver was removed for gross and histological examination. Results: The mean values of serum alanine-aminotransferase (ALT) in groups A, B and C were 28.16±7.13, 82.33±10.89 and 49.66±6.12 U/L respectively, whereas, the mean values of gamma-glutamyl transferase (GGT) in groups A, B and C were 27.33±3.05, 79.33±4.37 and 45.66±1.85 U/L respectively. ANOVA showed significant (p<0.05) difference in mean value of these serum enzymes among groups. Post Hoc test, using the Tukey honestly significant difference (HSD) showed that there was significant (p<0.05) increase in mean value of ALT and GGT in group B as compared to group A and C. This test also showed that there was significant (p<0.05) decrease in mean value of these enzymes in-group C as compared to group B. Conclusion: Silymarin tends to normalise liver function test in alcoholic liver disease. Keywords: Ethanol, Silymarin, Alanine-aminotransferase (ALT), Gamma-glutamyl transferase (GGT)